Prevalence and association of compliance with the Canadian 24-hour movement guidelines with sociodemographic aspects in Brazilian adults: a cross-sectional epidemiological study - Leandro Dragueta Delfino; William Rodrigues Tebar; Diego Giulliano Destro Christofaro (BMC, 2024)
Abstract Background The physical inactivity is a global health concern, so that recommendations on sufficient physical activity levels are elaborated worldwide, such as in Brazil. However, the Canadian 24-Hour Movement Guidelines were first in the world to consider time-specific recommendations for physical activity, sedentary behavior and sleep, which is still not developed for Latin-American population. The present study aimed to verify the adherence to Canadian 24-hour guidelines in a Brazilian inner city and to analyze its association with sociodemographic aspects. Methods A cross-sectional epidemiological study, with a sample composed by 250 adults (140 women), with a median age of 41.0 years. Objective measures of moderate-to-vigorous physical activity (MVPA) and sedentary behavior were collected by accelerometry. Sleep duration and sociodemographic aspects (ethnicity, gender, age, educational attainment and socioeconomic level) were obtained through a face-to-face questionnaire. Canadian 24-hour guidelines considered ≥ 150 min/week of MVPA, <8 h/day of sedentary behavior and daily sleep time between 7 and 9 h, being analyzed separately and in combination. Poisson regression with robust variance estimator was used to analyze the prevalence ratio (PR) of meeting the 24-hour guidelines according to the categories of sociodemographic variables, being performed by the software IBM SPSS version 25.0. Results The complete 24-hour guidelines were met only by 24.4% of sample (n = 61). Sedentary behavior was the most met guideline (88%), followed by MVPA (56.8%) and sleep (53.2%), without significant difference according to sex. When compared to elderly participants, those participants in younger groups (18-39 years and 40-59 years) were more likely to meet MVPA guideline (PR = 2.51 [95%CI = 1.47; 4.28] and PR = 2.60 [95%CI = 1.52; 4.45], respectively), as well as the combination of MVPA and sedentary behavior (PR = 1.98 [95%CI = 1.13; 3.44] and PR = 2.17 [95%CI = 1.25; 3.79], respectively) and MVPA with the sleep guideline (PR = 2.39 [95%CI = 1.09; 5.27] only for 18-39 years group). Men were more likely to meet MVPA guideline than women (PR = 1.29 [95%CI = 1.04; 1.59]). Conclusion Younger aged and male adults were more likely to meet the Canadian 24-hour guidelines in a small Brazilian city. However, further studies with larger and representative samples of sociodemographic stratum are still needed.